Virulence analysis of Pyricularia oryzae isolates causing wheat blast in Bangladesh (Dhaka University Journal of Biological Sciences, 2021)
Mycology and Plant Pathology Laboratory, Department of Botany, University of Dhaka, Dhaka-1000, BangladeshPyricularia oryzae pathotype Triticum, causal agent of wheat blast, has emerged in Bangladesh as a serious threat for wheat production. Virulence analysis of plant pathogen can reveal the pathogenic nature of that pathogen. In the present study, twenty-four monoconidial isolates of P. oryzae from Chuadanga, Meherpur, Kustia and Jhenaidaha districts of Bangladesh were analyzed to observe their pathogenic potential. Based on the disease reactions, all the isolates were grouped into 3 pathotypes. Present investigation revealed that the isolates with high virulence were prevalent in the studied P. oryzae population. Again, Pathotype 1 that was identified as the most virulent can be used as reference for screening resistant wheat varieties.Dhaka Univ. J. Biol. Sci. 30(2): 151-157, 2021 (July)